MEANING OF LIFE THREE AMAZING THINGS ABOUT YOU AND 728 HARI - Dita, Elsa (CULTURAL EDUCATION JOURNAL OF LITERATURE AND CULTURE, 2020)
Abstract This thesis entitled "Meaning of Life on the Leading Character in Mansell™s Three Amazing Things about You and Oesman™s 728 Hari : A Comparative Literature Analysis ". This thesis discusses about meaning of life that can be seen by three areas of activity. There are two problems that focused in this thesis; meaning of life portrayed in the novel Three Amazing Things about You by Jill Mansell and 728 Hari by Djono W. Oesman and the similarities and the differences of meaning of life portrayed in the both of the novels. The method of research that is used in this thesis is qualitative method. Both of the novels are the primary source of data by using theory logotherapy by Viktor Emil Frankl and theory comparative literature which is will be compare in this study. The purpose of this thesis is to find out how meaning of life and how the similarities and the differences of meaning of life are portrayed in the both of the novels. From this research it is found that meaning of life can be prove from three areas of activity that potentially contain values, they  are, creative values, experiential values and attitudinal values that portrayed in both of novels. Keywords: meaning of life, comparative, literature